ANALISIS PENGARUH RASIO KEUANGAN TERHADAP PERTUMBUHAN LABA PADA PD. BPR ROKAN HULU - Makmur., Novia Hera, Andi Afrizal, (Jurnal Mahasiswa Prodi Manajemen Fakultas Ekonomi, 2016)
This research aims to see money ratio effect in parcial although coincide to profit development PD. BPR Rokan Hulu. The main purpose of company is to maximize profit. In company profit very necessary because have benefit for company dinectness because have benefit for company dinectness. One of theparameter company performance is profit. Profit which has from result profit company every year so could influence investation decision of investor. Profit development is increase although decrease of profit in every year, money ratio which used in thisresearch is cash ratio, primery ratio, gross profit margin. Technique analisys which used in this research is analysis multiple linier regression. The consclusion in this research show in parcial, cash ratio, primary ratio, gross profit margin doesn’t have significant influence toward profit development with significant value every money ratio is cash ratio 0,755, primary ratio 0,979, and gross profit margin 0,655. In coincide or simultaneous, cash ratio, primary ratio, gross profit margin also doesn’t have significant influence toward profit development with significant value 0,878.